ANÁLISE EXPERIMENTAL DE LAJE NERVURADA TRELIÇADA COM INCORPORAÇÃO DE FÔRMA INTERMITENTE EM PERFIL FORMADO A FRIO - Candido, Daniel Carvalho de Moura (2021)
The structural engineering market aims to solve a portion of infrastructure issues in society. As such, structural solutions are constantly developed to meet an everincreasing demand for controlling execution time, cost and environmental impact of business endeavors. In order to fulfil said demand, solutions for efficient floor systems that propose the use of intermittent steel formwork in the lower surface of a slab, which consists of uniformly spaced ribs. The space between ribs is filled by superposition of steel profiles or structurally inert elements, in similar fashion to reinforced concrete unidirectional ribbed slabs. This research investigates the flexural behavior of a trussed floor system called Trelifácil®, in which traditional precast reinforced concrete (RC) lattice joists are replaced with trussed rebar fastened inside a cold formed steel channel by uniformly distributed plastic spacers. The flexural strength was determined by means of a series of laboratory tests on full-scale specimens, considering constructions and serviceability phases. Two sets of four-point bending tests were conducted on specimens that represent the system during construction, one of which consisting of the isolated U channel profile and the other featured specimens with rebar trusses fastened to the profiles to evaluate the contribution of this element to the strength and flexural stiffness of the system during construction. The failure mode of the specimens was dependent on the proportion between the length with constant bending moment and the length of the specimens, as well as the relation between the latter and the width of the widest cross-section element. Among profile specimens, shorter lengths presented failure by distortion of the cross-section outside of the bending moment length, and medium lengths presented distortions at midspan and at the support, while longer specimens failed by cross-sectional distortions at midspan. The specimens featuring the U profile and truss presented similar dependency of the geometric properties, with shorter and medium lengths presenting different failure modes for the profile without loss of bearing capacity, until the definitive collapse, consisting of diagonal buckling of truss outside the length of constant bending moment. Long specimens exhibited failure by instability of the upper chord, immediately followed by distortion of the cross section at midspan. Furthermore, the bending moments equivalent to the maximum experimental loads obtained were compared with the characteristic resistance to bending moment obtained with the direct strength method and presented significant divergence. A third set of four-point bending tests were conducted on reinforced concrete slabs with incorporation of the Trelifácil® system to evaluate the contribution of each component to the strength and stiffness of the system during serviceability. Overall, all specimens presented failure by what could be classified as a plastic hinge inside the constant bending moment length and the registered slip between steel and concrete was not considerable. The maximum experimental loads observed presented similar value to an analytical proposal that considers the system as a reinforced concrete tee with the steel profile acting as additional positive steel reinforcement.